《左传》受益表达 = Benefactive in Zuo Zhuan - 蔡燕凤 Chai, Yen Fong (2012)
受益概念在语言结构的分析中一般都属于边缘格，因而学界对它的研究向来甚少，而上古汉语的受益研究更是缺乏。本文立足于Zúñiga & Kittilä（2010）和 Valin & LaPolla（1997）的研究，首先从形式和意义上介绍目前和受益有关的研究成果，并在这个基础上以《左传》为考察对象，探讨上古汉语的受益表达。《左传》在编码受益概念上采用了几种不同的句法形式，如双宾、介词“于/於”、介词“为” 和“与”。本文的初步结论如下：一、上古汉语的双宾句式和“V+DO+于/於+IO”都能用以表达给予和受益事件，体现了类型学上的受益者标记经常和接受者标记同形的特点。比较这两种句式的语义，可发现双宾和“V+DO+于/於+IO”在事件施益方向上是相反的。前者受益事件一般是按参与者地位由上而下的施益； 后者的受益事件则是由下往上的施益。二、通过介词“为”和“与”的语法功能与来源，结合Croft（1991）的“致使顺序假说”和张敏（2008）的语义地图可发现受益者是兼具前项和Croft理论当中后项性质的语义角色。Benefactive is regarded as oblique case in structure analysis. Hence, research regarding the topic has been lacking, regardless in the other languages or the Archaic Chinese. Based on the research completed by Zuniga & Kittila (2010) and Van Valin & LaPolla (1997), we will first introduce the current achievement of the research completed to date, pertaining to perspective of form and meaning of the verb phrases. To allow better illustration on the study, Zuo Zhuan will be used as the research materials for discussing the benefactive coding of the Archiac Chinese. There are several benefactive codings in Zuo Zhuan which include the double object construction, Yu construction, and the prepositions Wei and Yu . Our conclusion of the research is shown as below: 1. Double object construction and Yu construction can be used to code both Give and Benefactive events, thus it reflects the feature of the similarity between the recipient marker and the beneficiary marker. Through comparing the meaning between the two constructions, we have discovered the difference on the direction of giving benefit between two constructions. The agent 's status of double object construction is always higher than the beneficiary 's status. Adversely, the agent 's status of Yu construction is always lower than the beneficiary status. 2. Through the syntactic function and function source of the prepositions Wei and Yu , as well as the correspondent between Causal Order Hypothesis as proposed by Croft(1991) and Zhang Min (2008) 's semantic map, this study leads us to the discovery of the fact that the meaning of beneficiary is not as simple as what we have perceived all the years.